Initiator‐Free, Multiphoton Polymerization of Gelatin Methacrylamide. Issue 12 (17th October 2018) - Parkatzidis, Kostas; Kabouraki, Elmina; Selimis, Alexandros; Kaliva, Maria; Ranella, Anthi; Farsari, Maria; Vamvakaki, Maria
Abstract: Multiphoton lithography (MPL), based on multiphoton polymerization (MPP), is a powerful technique for the fabrication of 3D structures used in tissue engineering and other biomedical applications, microoptics, nanophotonics, micro‐/nanomechanics, and micro‐/nanofluidics. MPL is based on the localized polymerization/cross‐linking of photosensitive materials induced by femtosecond laser pulses. The use of an appropriate photoinitiator (PI) is required to initiate the polymerization/cross‐linking process. However, several studies have demonstrated the cytotoxicity of the PIs and their derived free radicals. The photo‐cross‐linking of a pre‐synthesized photosensitive gelatin methacrylamide (GelMA) biopolymer using an initiator‐free MPP process is reported for the first time. This is achieved by employing a femtosecond laser operating in the visible range of the spectrum (520 nm). It is demonstrated that multiphoton absorption can cause the cleavage of the polymer double bonds and induce the cross‐linking process. GelMA‐based 3D structures accurately replicating the original computer‐aided design are fabricated, and their excellent biocompatibility is demonstrated in vitro using 3D cell culture experiments with NIH‐3T3 fibroblast cells. Abstract : Three‐dimensional structures based on gelatin methacrylamide are fabricated by initiator‐free multiphoton polymerization using a femtosecond laser operating in the visible range. The elimination of the toxic photoinitiator and its derived free radicals renders the approach very attractive in 3D scaffold fabrication.